The Tumor Suppressor Kinase LKB1: Metabolic Nexus - Bourouh, Mohammed; Marignani, Paola A. (Frontiers in Cell and Developmental Biology, 2022)
Liver kinase B1 (LKB1) is a multitasking tumor suppressor kinase that is implicated in multiple malignancies such as lung, gastrointestinal, pancreatic, and breast. LKB1 was first identified as the gene responsible for Peutz-Jeghers syndrome (PJS) characterized by hamartomatous polyps and oral mucotaneous pigmentation. LKB1 functions to activate AMP-activated protein kinase (AMPK) during energy stress to shift metabolic processes from active anabolic pathways to active catabolic pathways to generate ATP. Genetic loss or inactivation of LKB1 promotes metabolic reprogramming and metabolic adaptations of cancer cells that fuel increased growth and division rates. As a result, LKB1 loss is associated with increased aggressiveness and treatment options for patients with LKB1 mutant tumors are limited. Recently, there has been new insights into the role LKB1 has on metabolic regulation and the identification of potential vulnerabilities in LKB1 mutant tumors. In this review, we discuss the tumor suppressive role of LKB1 and the impact LKB1 loss has on metabolic reprograming in cancer cells, with a focus on lung cancer. We also discuss potential therapeutic avenues to treat malignancies associated with LKB1 loss by targeting aberrant metabolic pathways associated with LKB1 loss.